Journeys of discovery in volunteer tourism : international case study perspectives - Lyons, Kevin D.; Wearing, Stephen (CAB books., 2008)
Offers an insight into how volunteer tourism is growing and developing. This title includes case studies from researchers in the field which explore the experiences of the volunteer tourist and the relationships between volunteers and host communities and commercial, non-commercial and government entities involved in volunteer tourism.